Effect of coffee on color stability and surface roughness of newly introduced single shade resin composite materials - Shaimaa Rohym; Hossam El Mandouh Tawfeek; Raghda Kamh (BMC, 2023)
Abstract Background Dentists started to follow the era of using single-shade resin composite restorations to avoid color shade selection. Our study was done to evaluate and compare the color stability of two single-shade resin composite materials. Methods Sixty samples were randomly allocated into two main groups (n = 30) according to the composite resin used: Group O: (Omnichroma) samples and Group V: (Venus Peral) samples. Each group was then divided into two subgroups (n = 15): group O1 and V1: samples immersed in coffee. Group O2 and V2: samples immersed in distilled water. Color changes (ΔE) and roughness values (Ra) were evaluated at baseline, first, and 14th days of immersion. The color change was assessed using Vita Easyshade V, while surface roughness was assessed using a profilometer and Atomic Force Microscope (AFM). Data were collected and statistically analyzed using two-way variance analysis (ANOVA) and Tukey's post-hoc test (p < 0.05). Results Group O1 and V1 recorded the highest ΔE00 (P = 0.002, 0.0001, respectively) and Ra values (P < 0.001) with no significant difference between both materials at 14 days. Conclusion Single shade resin composite with innovative chromatic material technology has dramatic color change and surface roughness that sacrifice esthetic success.